Digital Financial Literacy, Finauancial Attitudes, and Financial Self-Efficacy in Relation to Financial Behavior among Micro, Small, and Medium Enterprise (MSME) Owners in Indonesia - Yoga Dava Akbar Argaputra; Mychelia Champaca (Indonesian Journal Publisher, 2026)
The rapid development of digital financial technology in Indonesia has not been fully accompanied by prudent financial behavior among micro, small, and medium enterprises (MSMEs), creating a gap between technology adoption and effective financial management. This study aims to examine the effects of Digital Financial Literacy, Financial Attitudes, and Financial Self-Efficacy on the financial behavior of MSME actors. A quantitative explanatory approach was employed using data collected from 300 MSME actors selected through purposive sampling. Data were obtained through a structured Likert-scale questionnaire and analyzed using multiple linear regression. The findings reveal that Digital Financial Literacy and Financial Self-Efficacy have positive and significant effects on financial behavior, whereas Financial Attitudes have no significant effect. These results suggest that technical competence in using digital financial services and confidence in managing financial resources play a more important role in shaping responsible financial behavior than positive financial attitudes alone. In conclusion, strengthening Digital Financial Literacy and Financial Self-Efficacy is essential for improving the financial behavior of MSME actors in Indonesia.